A extrafiscalidade como instrumento para a realização da justiça tributária : fundamentos e limites - Bastos, Judson Gomes da Silva (2022)
This work focuses on the study about the promotional function of Tributary Law, and its perspective is focus on the using of extrafiscal rules with the purpose of achieving tributary justice. In this sense, the extrafiscal rules that can bring significant contributions to achieving tributary justice were examined. This work proposes to fulfill three tasks: the first refers to the analysis of the promotional function of Law and the role of the legislator in the construction of a promotional system. The second seeks to do a correlate the promotional function of Tributary Law through tributary induction rules (extrafiscality) that served as an instrument for the State to comply with its objectives and foundations. The third task that is proposed is to verify if the extrafiscal function of the tributary rule is the way to tributary justice. Regarding the methodological part of the research. We opted for the bibliographic research procedure to evidence the use of induction norms and the application of tributary principles related to justice and the effectiveness of the objectives and foundations of the State, as well as the analysis of the results of the application of inductive tributary norms.The research allowed us to show that the use of the extrafiscal rules offers important contributions as a normative instrument for the State to fulfill its fundamental objectives and can be a path to tributary justice, despite the limitations that involve its application.